(untitled) (Journal of Oriental Studies, 2017)
The article gives an analysis of Iran’s nuclear program in the context of relations with the international community. Iran’s cooperation with international organizations according to its nuclear policyhas a great importance, especially in the light of the lifting of the latest political sanctions of Europe and the US directed against Iran’s nuclear program. There are many contradictions between the United States and Iran as «virtual nuclear state»,developing nuclear technologies, as well as the enrichment of uranium for peaceful purposes. The interaction of Iran with international communities, in which both sides are interested, alleviates these contradictions and promotes closer cooperation and compromises in their further cooperation.